2003
DOI: 10.1097/01.brs.0000068242.29809.d0
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Quantitative Segmental Analysis of Scoliosis Corrected by the In Situ Contouring Technique

Abstract: Three-dimensional reconstruction of the spine allows quantitative segmental analysis of the deformity. This could be used as a reliable tool to evaluate both the severity of the scoliosis and the effects of the surgical correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…On the other hand, segmental intervertebral rotation could also be evaluated based on 3D reconstructions [35]. Nevertheless, for obtaining a highly accurate 3D reconstruction, the precisely perpendicular placement of frontal and lateral X-ray detectors and proper patient positioning during imaging are essential.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, segmental intervertebral rotation could also be evaluated based on 3D reconstructions [35]. Nevertheless, for obtaining a highly accurate 3D reconstruction, the precisely perpendicular placement of frontal and lateral X-ray detectors and proper patient positioning during imaging are essential.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this 3D reconstruction allows the segmental quantitative Table 1 for measurement values analysis of rotational deformities [22,23]. For the highest possible accuracy and reliability of 3D reconstruction-based measurements, the precisely orthogonal acquisition of biplanar X-rays and correct patient positioning are of critical importance [23].…”
Section: Discussionmentioning
confidence: 99%
“…They reconstructed 3D models using bi-planar radiographs, and examined the difference among four operative methods. Steib et al also performed 3D studies about the 3D change before and after surgical correction by in situ contouring technique using the reconstructed 3D models from bi-planar radiographs [6,7,16,27]. However, these methods lacked accuracy since their method required only about 6-20 landmarks when reconstructing the bone models.…”
Section: Intervertebral Axial Rotationmentioning
confidence: 99%
“…Although there have been some studies regarding intervertebral deviation of AIS [5,7,24], no detailed 3D study using an in vivo model of AIS has been reported. Therefore, the present study aimed to develop a local coordinate system for the AIS vertebra and to evaluate the in vivo 3D intervertebral deviation in the coronal, axial and sagittal planes in order to provide guidance for its surgical correction.…”
Section: Introductionmentioning
confidence: 99%